IMPROVING ELEMENTARY SCHOOL TEACHERS’ COMPETENCE THROUGH THE NUMBERED HEAD TOGETHER METHOD AT SD OF TAMBANG SUB-DISTRICTS IN KAMPAR - Endang Purwanti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper reports the improvement of teacher competence in a teacher work programme at Sub-Districts Tambang elementary school in Kampar through numbered head together method based on the background of the problem. Hence, the formulation of the problem is "Can the numbered head together method increase elementary school teacher competence at SD Tambang Sub-Districts in Kampar?". The research is a school action research (SAR). The Kemmis and Mc. Taggart’s model is a spiral from one to another further cycle. The research subjects were teachers at an elementary school in the Tambang sub-district of Kampar. The number of classroom teachers who were the subjects of the research was 12 school principals who were at SD Tambang sub-districts in Kampar. Based on the results of the analysis and discussion, it can be concluded that the numbered head-together method can improve teacher competence. Through numbered head-together method, teachers’ activity becomes more active and teachers tend to be positive to follow the teaching and learning process conducted by the researcher or in the implementation. In cycle I, it can be seen that the teachers’ teaching competence was still relatively good with an average score of 70.29. While the results in cycle II, teachers’ teaching competence reached an average score of 79.52, which was classified as very good.